Refractory Epstein-Barr Virus (EBV)-Related Post-transplant Lymphoproliferative Disease: Cure by Combined Brentuximab Vedotin and Allogeneic EBV-Specific T-Lymphocytes - Mika, Thomas; Strate, Katharina; Ladigan, Swetlana; Aigner, Clemens; Schlegel, Uwe; Tischoff, Iris; Tischer-Zimmermann, Sabine; Eiz-Vesper, Britta; Maecker-Kolhoff, Britta; Schroers, Roland (Frontiers in Medicine, 2019)
Post-transplant lymphoproliferative disease (PTLD) represents serious complication after allogeneic hematopoietic stem cell transplantation (alloHSCT). Previously, survival rates of PTLD have improved due to the introduction of rituximab. However, reports on curative management of refractory PTLD are scarce. Today there is no consensus how to treat rituximab-refractory PTLD, especially in highly aggressive disease. Here, we describe successful management of refractory EBV-associated PTLD, specifically DLBCL, with combined brentuximab vedotin and third-party EBV-specific T-cells in a multidisciplinary treatment approach.